1980
DOI: 10.3382/ps.0590164
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival of Cock Spermatozoa In Vitro with Fluid Removed from Tissue Cultured Oviducal Cells

Abstract: When cock spermatozoa were incubated at 41 C with fluid removed from tissue cultured oviducal cells, their motility, assessed at room temperature, was maintained for 4 or 5 days. Fertilizing ability was retained for one week after culture for two days at 41 C. These results were comparable to the duration of motility and fertilizing ability of spermatozoa incubated in the presence of cultured oviducal cells. The results indicated that the fluid removed from the tissue cultured cells contains a secretory produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Considering the fertility results for the three groups of spermatozoa incubated for either 6 or 24 hr, MEM alone appears to be as beneficial as TCF or the presence of TCC in maintaining in vitro sperm survival at 41 C. This observation is contrary to those of Ashizawa et al (1976), Ashizawa and Nishiyama (1977a), and Fujihara and Howarth (1980), all of whom reported that spermatozoa incubated in MEM alone had little or no fertilizing ability following surgical insemination. An explanation for these contrasting results may be the longer sperm incubation periods of 2 and 4 days used in these studies as compared to the shorter incubation periods of 6 and 24 hr used in the present studies.…”
Section: Preservation Of Cock Semenmentioning
confidence: 79%
See 2 more Smart Citations
“…Considering the fertility results for the three groups of spermatozoa incubated for either 6 or 24 hr, MEM alone appears to be as beneficial as TCF or the presence of TCC in maintaining in vitro sperm survival at 41 C. This observation is contrary to those of Ashizawa et al (1976), Ashizawa and Nishiyama (1977a), and Fujihara and Howarth (1980), all of whom reported that spermatozoa incubated in MEM alone had little or no fertilizing ability following surgical insemination. An explanation for these contrasting results may be the longer sperm incubation periods of 2 and 4 days used in these studies as compared to the shorter incubation periods of 6 and 24 hr used in the present studies.…”
Section: Preservation Of Cock Semenmentioning
confidence: 79%
“…Cells to be cultured were obtained from whole 9-day-old chick embryos. Cell preparation and culture were carried out according to the method described by Fujihara and Howarth (1980). The culture medium referred to as minimum essential medium (MEM) consisted of nine parts MEM (Eagle modified autoclavable medium with Earle's salts-#F-17 obtained from Grand Island Biological Company) and one part heat inactivated (56 C for 30 min) fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have since reported that fowl spermatozoa can survive at 41°C for 5 to 6 d when co-cultured either with dispersed somatic cells from various tissues from different species (Ashizawa et al, 1982 or for up to 11 d in expiants of oviducal tissue . It has also been reported that fowl spermatozoa can survive up to 4 d in cell-free media recovered from cell cultures (Fujihara and Howarth, 1980;Fujihara and Koga, 1982). Because cells and their products appear to maintain spermatozoal viability, the use of cell culture for short-term storage of semen is intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, fowl spermatozoa incubated with various types of cultured cells, such as cells from the fowl kidney, the skeletal muscle of a 9-day chick embryo, and HeLa and BHK-21 cells, survived for approximately 5 to 7 days, even at 41 C (Ashizawa and Nishiyama, 1977;Fujihara and Howarth, 1980;Ashizawa et al, 1982).…”
Section: Introductionmentioning
confidence: 99%